INSIDEN SINDROM PREMENSTRUASI PADA MAHASISWI KEPERAWATAN - Adin Mu’afiro; Kiaonarni O.W.; Irine Christiany (Poltekkes Kemenkes Surabaya, 2016)
This research is descriptive. Subjects were Nursing student of Polytechnic Of Health Ministry Surabaya using simple random sampling. Variable study was the incidence of premenstrual syndrome. Instruments used checklist PMS. The results showed that the entire student experience PMS symptoms with varying degrees of severity are not the same. Minor complaints on symptoms: breast pain (60%), Hard concentration (50%) and Insomnia (40%). Complaints are the symptoms: Joint pain / muscle and sudden mood changes (80%), Irritability (60%), abdominal cramps (40%). Complaints weight on symptoms: headache (40%) and flatulence (30%). The onset of these symptoms are caused due to consumption of calcium and magnesium mahasisiwi not fulfilled the needs of the appropriate RDA (calcium = 1000mg / hr; magnesium 200mg / hr). Mostly (60%) only consume calcium 200-300 mg / hr, and no student who consume magnesium. Students who have PMS to record her menstrual period for 3 months when the symptoms are felt natural. Key words: premenstrual syndrome, nursing student